EFEKTIVITAS PROGRAM COMMUNITY EMPOWERMENT DALAM PENINGKATAN EKONOMI MASYARAKAT LOKAL DI KABUPATEN BOJONEGORO - Mifta Hulaikah; Moh Muhajir (MIYAH : Jurnal Studi Islam, 2017)
The purpose of this research is to analyze influences of community empowerment program to economic improvement of the local society, the effectively of this program, and the factor which support and which is not. This research is kind of mix method research with design Explanatory Sequential Design. There is two phase, which the first phase is quantitative, the second one is qualitative. The sampling in quantitative phase is 45, who the member of this programe. In qualitative phase, there is 3 people who was interviewed. This research is use regretion analyze. The result of this research shows that there is positive significant effect in empowering programe (training & facilities) to economic improvement. The training give more effect thanÂ  facilitate in improve the economic. The effectively of this program is 53%. This programe support by demography and economic structure of society. The factor which not support is the mind set of the society.Keywords: Community Empowerment, Local Society